2021
DOI: 10.21203/rs.3.rs-798060/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interpreting models interpreting brain dynamics

Abstract: Brain dynamics are highly complex and yet hold the key to understanding brain function and dysfunction. The dynamics captured by resting-state functional magnetic resonance imaging data are noisy, high-dimensional, and not readily interpretable. The typical approach of reducing this data to low-dimensional features and focusing on the most predictive features comes with strong assumptions and can miss essential aspects of the underlying dynamics. In contrast, introspection of discriminatively trained deep lear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 61 publications
3
9
0
Order By: Relevance
“…We identified a number of brain network pairs useful to the classification of SZ and HCs. Previous studies have found widespread effects of SZ upon the CBN [2][15][27], SMN [15], and SCN [2] similar to our results. Additionally, some studies have identified differences in the VSN/VSN [25][58], VSN/SCN [25][59], and VSN/SMN [25][60] as important to differentiating SZ from healthy individuals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We identified a number of brain network pairs useful to the classification of SZ and HCs. Previous studies have found widespread effects of SZ upon the CBN [2][15][27], SMN [15], and SCN [2] similar to our results. Additionally, some studies have identified differences in the VSN/VSN [25][58], VSN/SCN [25][59], and VSN/SMN [25][60] as important to differentiating SZ from healthy individuals.…”
Section: Discussionsupporting
confidence: 92%
“…This would indicate that the aberrant effects of SZ upon brain network interactions tend to be temporally localized. This finding is supported by [15], which found similar effects of SZ upon attention values of a long short-term memory network. Additionally, this finding is related to those of other studies that have found effects of SZ upon brain network dynamics [24], [26].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We only examined spatial differences in LRP relevance between groups. Future iterations might examine temporal differences in relevance between subtypes [9], [10]. Additionally, it might be helpful to apply a clustering explainability approach to quantify the relative importance of each network pair to each SZ subtype using a modified version of the methods used in existing studies [7], [11].…”
Section: Limitations and Next Stepsmentioning
confidence: 99%